Proses Berpikir pada Pemahaman Matematik Siswa Sekolah Dasar Terkait Materi Operasi Hitung Perkalian dan Pembagian Pecahan: The Process of Thinking in Mathematical Understanding of Primary School Students Regarding Counting Operation Materials Multiplicat - Sidik, Geri Syahril; Nugraha, Fajar (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of writing this article is to obtain an overview of the thinking process of ele- mentary school students in mathematical understanding related to the material of multi- plication and fraction distribution. The thought process consists of instrumental thinking processes and instrumental relational thinking processes. This research is a qualitative descriptive study. Students in one class are given a task sheet to do individually by writing clear work steps. Six students were selected as research subjects to analyze. Consisting of 2 subjects who have high math skills, 2 medium and 2 low. The process of thinking of a subject is observed by looking at and reviewing the answers to the assignment sheet and giving clinical interviews related to the results of his work. Based on data analysis, it was obtained an illustration that the subject did not have a good instrumental relational think- ing process. Generally, many subjects do not understand the concept of fractions, so it is wrong to change fractions to other forms, operate fractions and conclude answers.